Lewd women and wicked witches : a study of the dynamics of male domination - Hester, Marianne, 1955- (Routledge, 1992)
This book focuses on the development of revolutionary feminist theory of male sexual violence in the present day, and the witch hunts of early modern Europe, in an analysis of male power over women.